HUBUNGAN KARAKTERISTIK PEKERJA, TINGKAT PENGETAHUAN K3, SIKAP K3, UNSAFE ACTION, DAN UNSAFE CONDITION DENGAN KECELAKAAN KERJA DI INDUSTRI PAKAN TERNAK SURABAYA - Mohammad Mirwan; Ahmad Naufal Arkan Syah (EnviroUS, 2022)
Occupational safety, health (K3) is the protection of workers, as well as the basic rights of workers. Based on this, it is necessary to identify unsafe actions, unsafe conditions and analyze the relationship between worker characteristics, K3 knowledge level, K3 attitudes towards work accidents in the Surabaya Livestock Feed Industry, so that the results of this study can be used as material for improving the K3 system. The purpose of this study was to determine the relationship between the characteristics of workers, the level of knowledge of K3, OHS attitudes. The conclusion of this study is that there is a relationship between tenure, unsafe action, unsafe condition and work accidents with values of 0.000; 0.001; 0.035, respectively, correlation coefficient -0.627; 0.574; 0.387. The relationship between years of service and work accidents, namely the higher the tenure of a person, the lower the accident rate with the strength of a strong relationship, the relationship between unsafe action and work accidents, namely the higher the unsafe action, the higher the accident rate with the strength of a strong relationship, the relationship between unsafe conditions and work accidents. work accidents, namely the higher the unsafe condition, the higher the accident rate with the strength of the weak relationship